A Multinomial Logistic Regression Model for Analyzing Attitudes towards Political Activities: A Case Study in Erbil/ Kurdistan Region of Iraq - Fatah, Khwazbeen Saida (Sulaimani Journal for Pure and Applied Sciences, 2013)
Regression models are considered as the most commonly used statistical analysis techniques to describe the functional relationships between a dependent variable (either continuous or categorical) and a set of independent variables based on samples from a particular population. In this paper, a Multinomial Logistic Regression Model is proposed to investigate the variations of multi ethnic-religious people towards political attitudes. This model is applied specifically to a case study conducted in Erbil in Kurdistan Region of Iraq, where multi-ethnic and religious groups live in. Results for statistical analysis show that the variations of ethnicity or religion have no much effect on the political attitudes for the majority of citizens of this region.
Keywords: Regression Analysis; Logistic Regression; Multinomial Logistic Regression